2008
DOI: 10.1097/mlr.0b013e31817fdf46
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Navigation in Colorectal Cancer Screening

Abstract: Study participant screening use and preference increased. Age and attitudes predicted outcomes. Randomized trials are needed to determine intervention impact at the population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 30 publications
1
102
0
1
Order By: Relevance
“…In previous studies on CRC screening intervention, higher attendance was achieved by some intervention practices such as health-care-provider-directed intervention [19] , telephone support [20,21] , psychoeducational intervention [22,23] , tailored guidance [24,25] , patient-physician communication [26] , motivational interviewing [27] , physician reminder [28,29] , community volunteers [30] , and mailed brochure [31] . However, one-sided intervention methods may not achieve a satisfactory effect among nonadherent high-risk subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on CRC screening intervention, higher attendance was achieved by some intervention practices such as health-care-provider-directed intervention [19] , telephone support [20,21] , psychoeducational intervention [22,23] , tailored guidance [24,25] , patient-physician communication [26] , motivational interviewing [27] , physician reminder [28,29] , community volunteers [30] , and mailed brochure [31] . However, one-sided intervention methods may not achieve a satisfactory effect among nonadherent high-risk subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Panel management has been shown to improve health outcomes among patients with a range of conditions, including lowering glycosylated hemoglobin levels in patients with diabetes [6][7][8], and improving smoking cessation rates [9] and self-reported quit attempts by patients who use tobacco products [10]. Panel management has also been shown to enhance care processes, increasing the rates of vaccination and bone density screenings [11], as well as screenings for colorectal and breast cancer [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…9 Further, in randomized controlled trials tailored interventions are more effective than nontailored interventions in enhancing sociopsychological factors across sociodemographic groups. [10][11][12][13][14][15][16][17][18][19][20][21][22] Whether enhancement of sociopsychological factors influences health behaviors is uncertain. 12,13,19,[22][23][24][25][26][27][28][29][30][31][32] Among trials comparing patients receiving sociopsychologically tailored colorectal cancer screening interventions with active control, 15,19,20,22,[25][26][27][28][29][30]33 only some found superior effects of tailoring 19,25,28,29,34 ; in all but 1 trial 34 screening was self-reported, 19,25,…”
Section: Introductionmentioning
confidence: 99%
“…57 Nonetheless, these EHBM factor effect sizes are comparable to those in published trials. [10][11][12][13][14][15][16][17][18][19][20][21][22] In our sample, a 1 SD increase in self-efficacy was associated with a 5.4% greater likelihood of screening (data not shown, available upon request). Thus, the IMCP self-efficacy effect size of 0.16 would be expected to translate into a less than 1% increase in screening (5.4% × 0.16 = 0.86%).…”
mentioning
confidence: 99%